Rancang Ulang Alat Penghalus Rebana untuk Meminimumkan Waktu Proses Penghalusan - Rozi, Fakhrur; Mundari, Siti (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
UMKM Surya Agung Percussion, located in Kaliwot Hamlet, RT 18, RW 07, Bungah Village, Bungah District, Gresik, is a micro, small, and medium-sized enterprise (UMKM) that produces percussion instruments such as tambourines. The products manufactured by UMKM Surya Agung Percussion include tambourines, hadrahs, marawis, and darbukas. The flagship product of this UMKM is the tambourine. In the production process, UMKM Surya Agung Percussion has a tambourine smoothing machine with a capacity of 50 pieces per day. However, the capacity of the machine is unable to meet the demand for tambourines, which can reach up to 400 pieces per week. Therefore, a study is conducted to observe this phenomenon with the aim of designing a tambourine smoothing tool to increase the production capacity of tambourines and minimize the smoothing process time. The tool is redesigned taking into account the anthropometric aspects of the workers to make it more ergonomic and produce a higher output than before to meet the fluctuating demand for tambourines.